2006
DOI: 10.1175/bams-87-7-891
|View full text |Cite
|
Sign up to set email alerts
|

Improving Global Analysis and Forecasting with AIRS

Abstract: T he NASA Atmospheric InfraRed Sounder (AIRS), the first of the new generation of meteorological advanced sounders for operational and research use, is part of a large international investment to upgrade the operational meteorological satellite systems. The new systems include the NOAA Crosstrack Infrared Sounder (CrIS) and the Hyperspectral Environmental Suite (HES) instruments, on U.S. operational polar-orbiting and geostationary platforms, respectively, and the Infrared Atmospheric Sounding TABLE I. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 5 publications
1
134
0
Order By: Relevance
“…Notice that not all channels from these instruments are used in the GEOS-5 DAS. For example, out of the set of 281 AIRS channels typically available for operations (Le Marshall et al, 2006) only the cloud-cleared ones are actually used in the in GEOS-5 DAS and the sensitivity is shown for the 152 channels used in the assimilation cycles performed in these experiments. The large negative sensitivity of channel 15 of AMSU-A suggests that error covariance inflation for this channel could prove beneficial to the forecasts.…”
Section: Preliminary Results With Nasa Geos-5 Dasmentioning
confidence: 99%
“…Notice that not all channels from these instruments are used in the GEOS-5 DAS. For example, out of the set of 281 AIRS channels typically available for operations (Le Marshall et al, 2006) only the cloud-cleared ones are actually used in the in GEOS-5 DAS and the sensitivity is shown for the 152 channels used in the assimilation cycles performed in these experiments. The large negative sensitivity of channel 15 of AMSU-A suggests that error covariance inflation for this channel could prove beneficial to the forecasts.…”
Section: Preliminary Results With Nasa Geos-5 Dasmentioning
confidence: 99%
“…Most of the NWP centers currently assimilate observations available from satellites to improve the tropospheric moisture analysis using variational methods. Satellite-measured infrared and microwave radiances have been shown to be beneficial to NWP model forecasts because they provide valuable information on atmospheric temperature and humidity [Derber and Wu, 1998;English et al, 2000;Bouttier and Kelly, 2001;Le Marshall et al, 2006;McNally et al, 2006]. The impact of assimilation of satellite data has strong regional dependency.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the recent years have shown that satellite data can also be valuable on a regional scale [Montmerle et al, 2007;Govindankutty et al, 2008;Reale et al, 2009;Stengel et al, 2009;Singh et al, 2010]. A number of variational data assimilation studies [Le Marshall et al, 2006;Garand et al, 2007;Reale et al, 2008;Singh et al, 2008;McCarty et al, 2009;Pu and Zhang, 2010;Rakesh et al, 2010;Zhou et al, 2010;Miyoshi and Kunii, 2012;Otkin, 2012;Singh et al, 2012;Kumar et al, 2013] have demonstrated that the inclusion of Atmospheric Infrared Sounder (AIRS) observations can improve the forecast skill of the model substantially due to its hyperspectral nature. These profiles are becoming increasingly important in operational weather forecasting and have advantage in identifying the fine thermal structure of the atmosphere in a number of studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provided NWP centres with four years experience with this data type before the first data from the true operational missions arrived (e.g. AulignĂ© et al, 2003;Collard et al, 2003;Le Marshall et al, 2006;McNally et al, 2006). AIRS measures the radiance emitted from the Earth in 2378 channels covering the spectral interval from 650 to 2665 cm −1 at a resolution of around 1 cm −1 .…”
Section: Introductionmentioning
confidence: 99%